Studies in Austral Bryaceae (Bryopsida). III. A Preliminary Account with Keys to Rosulabryum J.R. Spence in Chile - John R. Spence (Pensoft Publishers, 2021)
A preliminary study of the genus Rosulabryum J.R. Spence in Chile is presented, with brief species descriptions, notes on ecology and distributions, and a taxonomic key. The following 12 species are confirmed with vouchered specimens; Rosulabryum andicola (Hook.) Ochyra, Rosulabryum billarderii (Schwägr.) J.R. Spence, Rosulabryum campylothecium (Taylor) J.R. Spence, Rosulabryum capillare (Hedw.) J.R. Spence, Rosulabryum coloratum (Müll. Hal.) J.R. Spence, Rosulabryum densifolium (Brid.) Ochyra, Rosulabryum longidens (Thér.) J.R. Spence, Rosulabryum macrophyllum (Cardot & Broth.) Ochyra, Rosulabryum perlimbatum (Cardot) Ochyra, Rosulabryum puconense (Herzog & Thér.) J.R. Spence, Rosulabryum rubens (Mitt.) J.R. Spence, and Rosulabryum torquescens (Bruch ex De Not.) J.R. Spence. Rosulabryum canariense (Brid.) Ochyra is tentatively excluded as the Chilean material can be referred to R. coloratum. Similarly, Rosulabryum viridescens (Welw. & Duby) Ochyra is tentatively excluded since the Chilean plants do not match the African type, but instead appear to be atypical plants of R. campylothecium.